Effectiveness of Minaraya Probiotics on The Growth Rate and Immune Response of Catfish (Clarias gariepinus) - ren fitriadi; Purnama Sukardi; reza Muhammad Riady; mohmammad nurhafid; Agnes Heratri; Maghfira Selia Irawati (PT. Artha GenetikaLab Indonesia, 2025)
The growing demand for catfish in the market is prompting farmers to consistently enhance their production capacity. Several obstacles are encountered during production growth, such as pathogen attacks, suboptimal growth, and low survival rates. This study aimed to determine the effectiveness of Minaraya probiotics with different doses in feed on the growth and immune response of catfish. The method used in this study was an experimental method with a completely randomized design (CRD) consisting of four treatments: control (without probiotics), and treatments P1, P2, and P3 with the addition of Minaraya probiotics at 2, 5, and 10 mL per 2.5 kg of feed, respectively, each with three replications. The parameters observed included survival rate, SGR, DGR, FCR, PER, AF, RB, and leukocyte differentiation. The results showed that the survival rate in all treatments was relatively high, ranging from 95% to 98.89%. The results also showed that the addition of Minaraya probiotics significantly (p<0.05) increased growth parameters (SGR and DGR) and feed efficiency (FCR and PER), with the best dose being in treatment 3 (P3) at a dose of 10 mL/2.5 kg of feed. On the other hand, the non-specific immune response also increased in the treatment given Minaraya probiotics, as indicated by increased phagocytic activity, respiratory burst, and proportion of lymphocytes, neutrophils, and monocytes, as well as an increase in the total number of erythrocytes after Aeromonas hydrophila infection. The application of Minaraya probiotics in a sustainable cultivation system can improve catfish productivity and health.